Altered gut microbiota by voluntary exercise induces high physical activity in high-fat diet mice - Eri Oyanagi; Masataka Uchida; Michael J. Kremenik; Hiromi Yano (Japanese Society of Physical Fitness and Sports Medicine, 2018)
In the present study, we determined whether or not exercise-induced high physical activity could be transmitted via altered gut microbiota. We collected cecal material from male C57BL/6N mice for 12 weeks under two conditions: voluntary wheel running (EX) and sedentary condition (SED). After depleting endogenous gut microbiota, cecal microbiota transplantation (CMT) was initiated in the recipient mice by placing cecal contents of either EX or SED mice into the oral cavity directly with the feeding of a high-fat diet (HFD). After a breeding period of 8 weeks, the physical activity test of the HFD (EX-CMT and SED-CMT) mice was examined. Although EX donor mice were attenuated with increasing body mass and body fat, and induced hypertrophy of the heart was compared with SED donor mice, those parameters did not show any difference between EX-CMT and SED-CMT mice. Nevertheless, high physical activity was observed in EX-CMT mice compared to SED-CMT mice (p < 0.01). These results suggest that exercise-induced high physical activity might be transmitted to un-exercised HFD mice via its altered gut microbiota.